Imagination and invention - Simondon, Gilbert (Univocal book., 2022)
"Here, in English translation for the first time, is Gilbert Simondon's fundamental reconception of the mental image and the theory of imagination and invention. Drawing on a vast range of mid-twentieth-century theoretical resources, this book provides a comprehensive account of the mental image and adds a vital new dimension to the theory of psychical individuation in Simondon's earlier, highly influential work"--